The stress levels of parents whose children are on antiretroviral therapy - Verster, Linley Joan (My University, 2010)
HIV is having devastating effects on Africa as a whole and more specifically on Sub-Saharan Africa. Children are vulnerable to the disease and in most cases being hit the hardest. Parenting at the best of times involves some form of stress, and caring for a chronically ill child increases the parenting stress levels. Antiretroviral treatment has a positive effect on children with HIV, however it is not well understood what effect antiretroviral treatment has on the parenting stress levels of the caregivers of children with HIV. The aim of the study was to establish whether caregivers of children diagnosed with HIV show a change in stress levels after commencement of anti-retroviral treatment for their children. The objectives of the study were: to determine if any of the subsections of the PSI-SF were affected by the commencement of antiretroviral treatment in the children; to determine if a correlation existed between the CD4 count of the child and the parenting stress level of the caregiver and to determine whether the age of the child impacted on the scores of the PSI-SF. The demographic data of the participants were also analysed. This study involved secondary analysis of existing data for the study "A longitudinal study of neurodevelopmental delay in HIV positive children" conducted by Joanne Potterton utilising a longitudinal pre-post test study design where participants were compared to their own baseline scores. The Parenting Stress Index Short Form (PSI-SF) was used to establish the parenting stress levels within its three different subsections. The PSI-SF was completed by the caregivers at visit one, two and three. These visits were to the Harriet Shezi Clinic at Chris Hani Baragwanath Hospital, Soweto, Johannesburg. The children were antiretroviral naïve at visit one, and at visit two which was six months later, they commenced antiretroviral treatment with a six months follow-up which was visit three. iv Forty-five participants were included in the study. The paired ‘t’ test showed a significant change (‘p’ = 0.02) in the subsections Parent Child Dysfunctional Interaction and Difficult Child(change in mean -3.31 and -2.78 respectively), while the subsection of Parenting Distress had no significant change between visit one and visit two (change in mean -2.09). The change in mean between visit two and three was -1.84 for the Parental Distress subsection, 0.6 for the Parenting Child Dysfunctional Interaction subsection and 0.8 for the Difficult Child subsection. The paired ‘t’ test was applied to visit one and three and the subsection Parenting Distress showed the greatest positive change of 'p' = 0.00 with a change in mean of -3.93. There was no correlation between the CD4 count of the child and the PSI of the caregiver at any of the visits (r=-0.2, 0.11,0.3, p=0.15, 0.5, 0.06 respectively). There was no correlation between the age of the child and the parenting stress of the caregiver at any of the visits (r=0.13,0.08,0.5 p=0.39,0.6 and 0.1 respectively). The stress levels of the caregivers decreased over the study period however there was no significant decrease with the commencement of antiretroviral treatment.
MSc Physiotherapy, Faculty of Health Sciences, University of the Witwatersrand, 2009
Keywords: parental stress; caregivers stress; antiretroviral therapy; children